2013
DOI: 10.4149/gpb_2013006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Leucine-rich repeat kinase 2 (LRRK2) and Parkinson protein 2 (parkin, PARK2) genes mutations in Slovak Parkinson disease patients

Abstract: Abstract. Parkinson disease (PD) is a chronic neurodegenerative movement disorder characterized by selective loss of nigrostriatal dopaminergic neurons and formation of Lewy bodies. Clinical manifestations include motor impairments involving tremor, bradykinesia, postural instability and rigidity.Using dHPLC method we screened exons 31, 35, 41, 48 of the Leucine-rich repeat kinase 2 (LRRK2) gene and exons 2, 6 and 7 of Parkinson protein 2 (parkin, PARK2) genes in a cohort of 216 consecutive, unrelated Slovak p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…[5][6][7][8][9] In genetic PD, several mutations centered on α-synuclein are reported and are responsible for protein misfolding and aggregation and mitochondrial dysfunction. 10,11 However, the majority of neuronal cell deaths are associated with exposure to environmental toxins such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and rotenone, which are widely used as herbicide parquet, insecticide, and fish poison. [12][13][14][15] Many studies have shown that activated microglial cells are key contributors to a variety of neurodegenerative disease progression, including PD and Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In genetic PD, several mutations centered on α-synuclein are reported and are responsible for protein misfolding and aggregation and mitochondrial dysfunction. 10,11 However, the majority of neuronal cell deaths are associated with exposure to environmental toxins such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and rotenone, which are widely used as herbicide parquet, insecticide, and fish poison. [12][13][14][15] Many studies have shown that activated microglial cells are key contributors to a variety of neurodegenerative disease progression, including PD and Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…The results were bimodal. Studies from nine countries (Austria, Greece, Hungary, India, Iran, Israel, Mexico, Slovakia, and the United States) reported zero G2385R carriers from a total sample of 1,367 PD cases [62,64,68,78,79,81,[87][88][89]. Studies from the other six countries yielded pooled prevalence estimates of 11.2% (Japan), 10.3% (China), 9.9% (South Korea), 9.7% (Taiwan), 5.9% (Singapore), and 1.2% (Kazakhstan) from a total sample of 13,087 PD cases [46][47][48]57,63,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107].…”
Section: G2385r and R1628pmentioning
confidence: 99%
“…The results for R1628P were also bimodal. Studies from seven countries (Hungary, Iran, Israel, Japan, Kazakhstan, Slovakia, and the United States) reported zero R1628P carriers from a total sample of 1,656 PD cases [48,57,62,64,78,81,87,108]. Studies from the other four countries yielded pooled prevalence estimates of 11.1% (Thailand), 7.5% (Taiwan), 5.4% (Singapore), and 5.3% (China) from a total sample of 6,264 PD cases [55,63,91,95,102,104,[109][110][111][112][113].…”
Section: G2385r and R1628pmentioning
confidence: 99%
“…Poole et al 2013;Hill et al 2014;Mancuso et al 2014) Parkinson's disease (i) Genetic susceptibility of a-synuclein(Polymeropoulos et al 1997), parkin(Kitada et al 1998;Paisan-Ruiz et al 2004), PINK1(Valente et al 2004) (ii) Mutation in leucine-rich repeat kinase 2 gene (LARK2)(Bognar et al 2013) (iii) Environmental toxin and ageing(Fahn 2003) (iv) Exposure to pesticide and metals(Semchuk et al 1992;Seidler et al 1996;Liou et al 1997;Gorell et al 1999a,b); Tanner et al 2011) (v) Transcriptional dysregulation (Yacoubian et al 2008) Friedreich's ataxia It is one of the most common of the hereditary ataxia syndromes (Gibilisco and Vogel 2013). It is caused by a large GAA-triplet-repeat expansion in the frataxin (FXN) gene, which results in deficiencies of frataxin, a mitochondrial protein involved in iron metabolism (Schulz et al 2009) Spinal muscular atrophy Mutation or deletion of survival neuron gene (SMN1) (Lorson et al 2010; Zanetta et al 2013) Amyotrophic lateral sclerosis Mutation in the superoxide dismutase type 1 (SOD1), TDP-43, FUS and ANG genes (Greenway et al 2004; Kwiatkowski et al 2009; Wegorzewska et al 2009).…”
mentioning
confidence: 99%